High prevalence of slight and mild hearing loss across mid-life: a cross-sectional national Australian study. (March 2019) - Wang, J.; Sung, V.; le Clercq, C.M.P.; Burt, R.A.; Carew, P.; Liu, R.S.; Mensah, F.K.; Gold, L.; Wake, M.
Abstract: Objectives: Although presbycusis typically becomes symptomatic only in older age, slight and mild hearing loss may be detectable well before this. We studied current prevalence and characteristics of hearing loss in Australian mid-life adults. Study design: This was a population-derived national cross-sectional study nested within the Longitudinal Study of Australian Children. Methods: A total of 1485 parents/guardians (87.3% female) aged 30–59 years underwent air-conduction audiometry. Hearing loss was defined in three ways to maximize cross-study comparability: high Fletcher index (mean of 1, 2 and 4 kHz; primary outcome relevant to speech perception), lower frequency (mean of 1 and 2 kHz) and higher frequency (mean of 4 and 8 kHz). Multivariable logistic regression examined how losses vary by age, sex and neighbourhood disadvantage. Results: On high Fletcher index, 27.3% had bilateral and 23.8% unilateral thresholds >15 dB hearing level (HL) (slight or worse), and 4.9% had bilateral and 6.3% unilateral thresholds >25 dB HL (mild or worse). Bilateral higher frequency losses were more common than lower frequency losses for thresholds >15 dB HL (30.9% vs. 26.4%) and >25 dB HL (11.0% vs. 4.6%). Age increased the risk of bilateral speech and higher frequency losses (all P for trend < 0.05), but not lower frequency losses >25 dB HL. Although sex was not associated with speech and lower frequency losses, men were more likely to have bilateral higher frequency losses (e.g. >15 dB HL: odds ratio [OR]: 2.2; 95% confidence interval [CI]: 1.5–3.2, P  < 0.001). Conclusions: Both slight and mild hearing loss show high and rising prevalence across mid-life. This offers opportunities to prevent progression to reduce the profound later burden of age-related hearing loss. Highlights: Around one in four Australian mid-life adults has slight or worse hearing loss. Around one in 20 has mild or worse hearing loss. Prevalence increases with age. Men are more likely to have higher frequency losses.